2010
DOI: 10.1111/j.1365-2656.2010.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of density and environmental factors on population fluctuations in a migratory passerine

Abstract: Summary 1.Populations of plants and animals typically fluctuate because of the combined effects of density-dependent and density-independent processes. The study of these processes is complicated by the fact that population sizes are typically not known exactly, because population counts are subject to sampling variance. Although the existence of sampling variance is broadly acknowledged, relatively few studies on time-series data have accounted for it, which can result in wrong inferences about population pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
1
42
1
Order By: Relevance
“…Although we show that populations' reproductive success are correlated with weather conditions in the breeding area, a recent meta-analysis found that fluctuations in population size were positively correlated with environmental conditions outside the breeding areas (Pasinelli et al 2011). This result supports the 'tubhypothesis' stating that population size is mainly limited by survival in the non-breeding season (Saether et al 2004).…”
Section: Carry-over Effects and Regulation Of Population Sizesupporting
confidence: 73%
“…Although we show that populations' reproductive success are correlated with weather conditions in the breeding area, a recent meta-analysis found that fluctuations in population size were positively correlated with environmental conditions outside the breeding areas (Pasinelli et al 2011). This result supports the 'tubhypothesis' stating that population size is mainly limited by survival in the non-breeding season (Saether et al 2004).…”
Section: Carry-over Effects and Regulation Of Population Sizesupporting
confidence: 73%
“…However, changes in population size are most responsive to habitat loss during the period in which populations are more severely limited [3]. Unfortunately, relatively few empirical studies provide quantitative evidence indicating whether population size of migratory species is more sensitive to the amount of breeding habitat or non-breeding habitat [7,34,35] and we are unaware of any study done at range-wide scales.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most empirical research on this subject has focused on documenting whether local populations experience limiting factors during the breeding season and to a lesser degree during the non-breeding season [7,8]. However, because limiting factors often vary across a species range [9] and through time, it is generally not possible to extrapolate from these local studies to understand range-wide population dynamics [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a 1969 paper R. Moreau, stated (notwithstanding the imposing two volumes of Nicoll and Meinertzhagen 1930) that Egypt south of Cairo and on both sides of the Nile Valley remained one of the worst-documented parts of Africa. The past years have seen a surge of interest in Egyptian ornithology and substantial areas of the country, hitherto unknown, have been surveyed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The past years have seen a surge of interest in Egyptian ornithology and substantial areas of the country, hitherto unknown, have been surveyed. The book "The birds of Egypt" (Goodman et al 1989) aimed to synthesize the new information on the birds of Egypt and to some extent re-evaluate the material available to Nicoll and Meinertzhagen (1930).…”
Section: Literature Reviewmentioning
confidence: 99%